Swiss lawmaking experience in ensuring the quality of laws - Akimzhanova М.T. (Bulletin of the Karaganda University “Law Series”, 2023)
Today, the stability of legislation determines the stability of the political and socio-economic course that the Republic of Kazakhstan has chosen for the development of the country as a whole. The stability of the legal regulation of public relations is achieved by the adoption of standard-setting bodies (officials), other subjects of standard-setting activities of measures aimed at ensuring the proper quality of regulatory legal acts, completeness and effectiveness of legal regulation of public relations, as well as aimed at limiting frequent adjustments of regulatory legal acts. The Constitution of the Republic of Kazakhstan has predetermined the need to ensure a unified legal space throughout its territory. In these conditions, it is especially important that the subjects of the law of legislative initiative and other rule-making bodies of the Republic of Kazakhstan observe the basic principles of the construction of normative legal acts. In order to effectively implement this task, adequate transformations are needed in the field of improving the system of knowledge of legislative technology and, first of all, strict compliance with the requirements that it provides for: the ordering and use of special legal means intended for the preparation of regulatory legal acts. In this regard, Swiss lawmaking is of interest in ensuring the quality of laws, where the points of contact of multilingual legislation are shown as an example. The purpose of the study is to study the experience of Switzerland’s rule-making activities and to develop recommendations aimed at improving the quality of legislation in the Republic of Kazakhstan. The methodological basis of the study was made up of general scientific methods of cognition of social phenomena and processes, methods of scientific analysis and synthesis.